Iron nitride nanoparticles for rapid dechlorination of mixed chlorinated ethene contamination - Brumovský, Miroslav; Micić, Vesna; Oborná, Jana; Filip, Jan; Hofmann, Thilo; Tunega, Daniel (Journal of hazardous materials, 2023)
Sulfidation and, more recently, nitriding have been recognized as promising modifications to enhance the selectivity of nanoscale zero-valent iron (nZVI) particles for trichloroethene (TCE). Herein, we investigated the performance of iron nitride (FexN) nanoparticles in the removal of a broader range of chlorinated ethenes (CEs), including tetrachloroethene (PCE), cis-1,2-dichloroethene (cis-DCE), and their mixture with TCE, and compared it to the performance of sulfidated nZVI (S-nZVI) prepared from the same precursor nZVI. Two distinct types of iron nitride (FexN) nanoparticles, containing γ'-Fe4N and ε-Fe2-3N phases, exhibited substantially higher PCE and cis-DCE dechlorination rates compared to S-nZVI. A similar effect was observed with a CE mixture, which was completely dechlorinated by both types of FexN nanoparticles within 10 days, whereas S-nZVI was able to remove only about half of the amount, most of which being TCE. Density functional theory calculations further revealed that the cleavage of the first C-Cl bond was the rate-limiting step for all CEs dechlorinated on the γ'-Fe4N(001) surface, with the reaction barriers of PCE and cis-DCE being 29.9, and 40.8 kJ mol-1, respectively. FexN nanoparticles proved to be highly effective in the remediation of PCE, cis-DCE, and mixed CE contamination.
Keywords: Iron nitride; Nanoparticles; Chlorinated ethenes; Sulfidation; Molecular modeling